Retrato das equipes de atenção primária à saúde do Brasil que possuem integração ensino-serviço - Jordão Júnior, Walace [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
The demand for comprehensive, person-centered care, based on an expanded concept of health, has led to the need for changes in health education. In this context, the Primary Health Care (PHC) service has stood out as a favorable setting for the development of various competencies. The update of curricular guidelines, in line with public health policies, has further encouraged the integration of students in training into these services. However, no national study has been identified in the literature that characterizes the PHC services that embrace this proposal of integration with health education. Therefore, the objective was to analyze the integration of trainees into primary health care teams across Brazil, creating a mechanism for disseminating their structural and organizational characteristics through an infographic. A case study with a quantitative, exploratory, and descriptive approach and a cross-sectional design was conducted. Secondary data from the external evaluation of the National Program for Access and Quality Improvement in Primary Care (PMAQ-AB) in 2018, throughout the national territory, were used. The case considered was the PHC services, and the variables of interest were the different levels of students integrated into the services. The exploratory variables selected included the structural and organizational characteristics of the services, as well as planning actions and community activities. Of the 36,355 teams that participated in the PMAQ-AB, nearly half reported no integration of teaching and service into their work routines (n=17,076; 46.7%). Among those reporting such integration, the Southeast region of the country had the highest concentration, with a focus on medical residency (61.5%). Across the country, undergraduate students (21%), followed by technical students (18%), were the most represented, with 54% of the teams having students from different educational levels. The results showed that 28.3% of the teams were trained in tutoring/preceptorship, and the majority were located in municipalities with fewer than 100,000 inhabitants (64.1%) and that had higher education institutions (61.5%), with a minority linked to teaching and research hospitals (16.5%). Most teams had a minimum composition (69.5%), including community health workers (99.5%). The majority used planning mechanisms to organize their practices (83.7%), although only 60% held weekly and/or biweekly meetings (59.8%). About 78% organized care to address territorial and user vulnerabilities, but only 15.6% discussed detected situations with schools. There was a predominance of health surveillance actions (average=94.0%), with fewer teams offering health promotion and disease prevention actions (average=59.6%). Regarding access and service quality, teams with a higher level of integration were concentrated among those with regular performance (32.0%), followed by good performance (30.6%). Thus, it is concluded that the identified structural profiles and organizational conditions may foster critical reflections and care practices more aligned with the principles of the SUS, reaffirming the importance of teaching-service integration as an essential strategy to qualify the training of health professionals and strengthen the SUS. At the same time, they highlight the lack of preparation among health professionals to act as preceptors, as well as an organization that tends to reproduce a still hegemonic care model focused on individual, disease-centered care rather than on health promotion actions. Keywords: Teaching Care Integration Services. Preceptorship. Primary health care. Health services.

A demanda por uma assistência integral, centrada na pessoa e no conceito ampliado de saúde determinou a necessidade de mudanças na formação em saúde. Nesse contexto, o serviço de Atenção Primária à Saúde (APS), destacou-se como cenário propício para a construção de diferentes competências. A atualização das diretrizes curriculares em consonância com as políticas públicas preconizadas na área da saúde estimulou ainda mais a inserção das pessoas em formação nestes serviços. Entretanto, não foi identificado na literatura nenhum estudo em âmbito nacional que caracterizasse os serviços de APS que acolhem esta proposta de integração com o ensino em saúde. Assim, objetivou-se analisar a integração de sujeitos em formação nas equipes de atenção primária à saúde em todo território brasileiro, criando um mecanismo de disseminação das suas características estruturais e organizacionais por meio de um infográfico retratar. Realizou-se um estudo de caso, de abordagem quantitativa com caráter exploratório e descritivo, e corte transversal. Utilizou-se dados secundários decorrentes da avaliação externa do Programa Nacional de Melhoria do Acesso e da Qualidade da Atenção Básica (PMAQ-AB), no ano de 2018, em todo o território nacional. Considerou-se como caso os serviços de APS e as variáveis de interesse foram os diferentes níveis de sujeitos do ensino que integram os serviços. Selecionou-se como variáveis exploratórias as características estruturais e organizacionais dos serviços, bem como as ações de planejamento e atividades comunitárias. Das 36.355 equipes que participaram do PMAQ-AB, quase metade informou não possuir integração ensino-serviço em suas rotinas de trabalho (n=17.076; 46,7%). Entre os que informaram tal integração, a região sudeste do país foi a que apresentou maior concentração, com destaque para a residência médica (61,5%). Em todo o país, os sujeitos em graduação (21%), seguido dos técnicos (18%) foram apontados em maior número, sendo que em 54% das equipes havia sujeitos de diferentes níveis de ensino. Os resultados evidenciaram que 28,3% das equipes foram qualificadas em tutoria/preceptoria e que a maioria das equipes estavam localizadas em municípios com <100 mil habitantes (64,1%) e que possuíam unidades de ensino superior (61,5%) e uma minoria com hospital de ensino e pesquisa (16,5%). Houve o predomínio de equipes com composição mínima (69,5%), que incluía agente comunitário (99,5%). A maioria utiliza mecanismos de planejamento para a organização de suas práticas (83,7%), apesar de só 60% realizar reuniões com periodicidade semanal e/ou quinzenal (59,8%). Cerca de 78% delas organizam atenção às vulnerabilidades do território e dos usuários, mas só 15,6% discute com a escola as situações detectadas nos educandos. Constatou-se predomínio das ações de vigilância em saúde (média=94,0%) e menor número das que ofertavam as de promoção em saúde e prevenção de agravos (média=59,6%). Em relação ao acesso e a qualidade dos serviços, as equipes que possuem maior número de integração se concentraram naquelas com desempenho regular (32,0%), seguido do bom (30,6%). Desta forma, conclui-se que os perfis estruturais e condições organizacionais identificadas podem fomentar reflexões críticas e práticas de cuidado mais coerentes com o preconizado do SUS reafirmando a importância da integração ensino-serviço como uma estratégia essencial para a qualificar a formação dos profissionais de saúde e o fortalecimento do SUS. Ao mesmo tempo, alertam para a falta de preparação dos profissionais de saúde para atuarem enquanto preceptores, assim como uma organização que tende a reproduzir um modelo de atenção ainda hegemônico, cujo foco se mantém no atendimento individual centrado na doença ao invés das ações de promoção à saúde.
Retrato de equipos de atención primaria a la salud en Brasil que tienen integración enseñanza-servicio
Analysis of the Primary Health Care Teams in Brazil that Integrate Teaching and Service
Keywords: Integração ensino-serviço; Preceptoria; Serviços de integração docente-assistencial; Atenção primária à saúde; Serviços de saúde